The Influence Of Socio-Demographics, Literacy, And Self-Identity On Adolescent Attitudes Towards Early Marriage In Sigi Regency - Nurhaviva, Nurhaviva; Abd. Rahman; Devi, Ratna; Rosmala Nur; Sridani, Ni Wayan (Jurnal KESANS : Kesehatan dan Sains, 2025)
Background: Child marriage in Sigi Regency has shown an increasing trend from year to year between 2020 and 2025. In 2020, a significant surge was recorded, which rose even more sharply in 2023. This increase is driven by various factors such as premarital pregnancy, economic pressure, and the influence of social media, especially in remote areas. Objective: To determine the influence of sociodemographic factors, literacy, and self-identity on adolescents’ attitudes toward early marriage in Sigi Regency. Method: This study employed a quantitative approach with a cross-sectional design. The research was conducted in three sub-districts in Sigi Regency: Dolo Barat, Dolo Selatan, and Marawola, with a total sample of 100 respondents. Results: The Wald Test results for the variables Last Education (p = 0.046), Income (p = 0.048), Culture (p = 0.002), Literacy (p = 0.035), and Self-Identity (p = 0.040) indicate that education, income, culture, literacy, and self-identity have a significant influence on adolescents’ attitudes toward early marriage in Sigi Regency. Culture emerged as the most dominant factor, followed by literacy, education, self-identity, and income. Adolescents with these favorable conditions are more likely to reject early marriage practices. Conclusion: The study shows that education, family income, culture, literacy, and self-identity significantly influence adolescents’ attitudes toward early marriage in Sigi Regency, with culture being the strongest factor influencing adolescents’ attitudes toward early marriage.